2020
DOI: 10.1111/ajt.15994
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of eIF5A hypusination by GC7, a preconditioning protocol to prevent brain death-induced renal injuries in a preclinical porcine kidney transplantation model

Abstract: Poitou-Charentes (convention number 15/RPC-R-017), Fondation de l'Avenir (Recherche Médicale Appliquée, program ET3-686) and Fondation pour la recherche médicale (FRM) (DPM 20121125559).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 69 publications
1
30
0
Order By: Relevance
“…We looked in vivo for the metabolic and main physiological effects associated to the overall modifications observed in vitro. Mice were treated daily with GC7 (IP, 3 mg/kg/day; "GC7" group) or with vehicle only (NaCl 0.9% w/v; "ctrl" group) for 72 h, according to the protocol demonstrated to have beneficial effect in rodent and pig models [13][14][15] . No difference was found between control and GC7 treated mice for sodium, potassium and chloride ion contents in plasma and urine ( Supplementary Fig.…”
Section: Impact Of Gc7 Treatment On Mice Physiological Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…We looked in vivo for the metabolic and main physiological effects associated to the overall modifications observed in vitro. Mice were treated daily with GC7 (IP, 3 mg/kg/day; "GC7" group) or with vehicle only (NaCl 0.9% w/v; "ctrl" group) for 72 h, according to the protocol demonstrated to have beneficial effect in rodent and pig models [13][14][15] . No difference was found between control and GC7 treated mice for sodium, potassium and chloride ion contents in plasma and urine ( Supplementary Fig.…”
Section: Impact Of Gc7 Treatment On Mice Physiological Parametersmentioning
confidence: 99%
“…Considering this new concept we have recently shown in mammals that the specific inhibition of eIF5A hypusination by the spermidine analogue N1-guanyl-1,7diamine-heptane (GC7) 12 is able to enhance the ischaemic tolerance both at the cellular and tissue level in a rat kidney model of ischaemia/reperfusion injury 13 . Based on these results, we successfully used GC7 both in a preclinical model of kidney transplantation in pig 14 and in a transient focal cerebral ischaemia (tFCI) model in mice 15 . Indeed, acute systemic administration of GC7 in the donor allowed better functional recovery of the kidney graft in the first case 13,14 and reduced the infarct volume, and motor and cognitive post-stroke deficits in the second 15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourthly, several reports in mammals have linked eIF5A with both cellular metabolism and respiration. In these studies, the inhibition of hypusinated eIF5A seems to reduce mitochondrial respiration, while leaving glycolytic ATP synthesis operative, which improves ischaemic conditions and organ transplantation [31][32][33]. Finally, and importantly, a recent report describes the modulation of mitochondrial respiration by eIF5A during macrophage activation [34].…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of the American Journal of Transplantation , Giraud and Kerforne et al use a preclinical model of porcine kidney transplantation to study the mechanisms of brain death‐induced AKI 1 . The same group previously reported that the eukaryotic initiation factor 5A (eIF5A) hypusination inhibitor N1‐guanyl‐1,7‐diaminoheptane (GC7), a spermidine analog, protects porcine kidneys from ischemic renal injury 2 .…”
mentioning
confidence: 99%